موقف الدولة الفاطمية من الصليبين دراسة في كتاب "النجوم الزاهرة لملوك مصر والقاهرة" للمؤرخ ابن تغري بردي(ت874ه/1469م) - SHARIF , LAMYA SHUKR MOHAMED; TAHA, ZAHIDA MUHAMMAD (Journal of Duhok University, 2023)
The Aim Of The Research Is To Present The Role Of Egypt During The Era Of The Fatimid State From The Crusader Invasion Of The Islamic East ,And To Explain The Position Of The Fatimids On The Formation Of The Crusaders Of The Crusader Entities In The Levant ,And The Role Of The Fatimid Ministry Institution In Directing The Path Of The Fatimid Caliphs ,Position On The Crusaders Through The  Book "The Bright Stars Of The Kings Of Egypt And Cairo" Which Is A Comprehensive Historical Encyclopedia Of The History Of Egypt Since The Islamic Conquest Until The Year (872islamiccalendar /1468 Christian Calendar) By The Historian Jamal Al-Din Abu Al – Mahasin, Known As Ibn Taghri Bardi ( 812-874 –Islamic Calendar  /1409-1469christian Calendar ) ,Who Is One Of The Most Prominent Historians Of Egypt In The Mamluk Era In The Nineteenth Century Ah/Fifteenth Century Ad ,The Historian Had Devoted A Large Part In His Book To Talk About The Crusader Invasion During The Fatimid Era And Reviewed In Its Folds The Position Of The Ruling Fatimid Authority In Egypt Regarding The Crusader Expansion In The Levant And The Like Threat To The Invasion And Control Of Egypt .